2017
DOI: 10.1186/s12909-017-1023-z
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported needs for improving the supervision competence of PhD supervisors from the medical sciences in Denmark

Abstract: BackgroundQuality of supervision is a major predictor for successful PhD projects. A survey showed that almost all PhD students in the Health Sciences in Denmark indicated that good supervision was important for the completion of their PhD study. Interestingly, approximately half of the students who withdrew from their program had experienced insufficient supervision. This led the Research Education Committee at the University of Copenhagen to recommend that supervisors further develop their supervision compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…Major markers of quality doctoral programs and supervisions might include the rates of completions versus attrition per cohort [4], reported quality of mentorship, support and supervision [5][6], quality of student-advisor relationship [7], duration of program completion, reported candidates/students satisfaction [8] quality of research output and publications [9], potential to contribute to the knowledge economy and overall measurable impact of doctoral education on the various walks of life as measurable in terms of innovations, solutions, quality of life and wellbeing. Unfortunately, most of these markers are generally rated between low and poor in many instances in Africa.…”
Section: Quality Of Supervisionmentioning
confidence: 99%
“…Major markers of quality doctoral programs and supervisions might include the rates of completions versus attrition per cohort [4], reported quality of mentorship, support and supervision [5][6], quality of student-advisor relationship [7], duration of program completion, reported candidates/students satisfaction [8] quality of research output and publications [9], potential to contribute to the knowledge economy and overall measurable impact of doctoral education on the various walks of life as measurable in terms of innovations, solutions, quality of life and wellbeing. Unfortunately, most of these markers are generally rated between low and poor in many instances in Africa.…”
Section: Quality Of Supervisionmentioning
confidence: 99%
“…Recently, a study explored the effect of a supervisor’s leadership style on the mental health of graduate students 3. Nearly half the doctoral students who withdrew from the doctoral program reported experiencing insufficient supervision, highlighting the fact that good supervision was important for completing the doctoral program 39,40. A survey in 2018 indicated that a weak relationship with a mentor is a common characteristic of most graduate students who experience anxiety and/or depression 21…”
Section: Introductionmentioning
confidence: 99%
“…Some of these barriers are reflected in the international literature, whilst some are new findings. General difficulties for students with a medical background initiating the writing process itself have also been found in previous research [3,4,20]. Specifically, lack of writing experience was found in a previous study, suggesting that PhD students with a medical background did not receive sufficient training in writing as part of their curriculum [20,21], although possible solutions were not evaluated.…”
Section: Barriersmentioning
confidence: 76%
“…Publication of results is a general requirement for all researchers, but writing the first scientific article for publication is still challenging for novices across all disciplines, including medical doctors [3]. An important challenge is the barrier to initiating the writing process itself.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation